Investigating the influence of fabrication parameters on the diameter and mechanical properties of polysulfone ultrafiltration hollow-fibre membranes - Rugbani, Ali (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.